Understanding Reasons That May Cause Attrition and Retention among English Language Teachers in a Developing Country - Yastıbaş, Ahmet Erdost; BATURAY, Meltem Huri; ERTAŞ, Abdullah (LPPM Universitas Advent Indonesia, 2022)
According to the literature, foreign language teacher attrition and retention (FLTAR) have been studied less, the studies on FLTAR have been made in developed countries more, and these studies have generally focused on the reasons of FLTAR. Therefore, the present study aimed to find out the reason(s) that may cause attrition and retention among foreign language teachers (i.e., English language teachers [EL]) in a developing country (i.e., Turkey). 100 Turkish EL teachers participated in this qualitative study. The data collected through a semi-structured written interview were content analyzed. According to the findings, there were three main groups of EL teachers with four or five sub-groups formed depending on the participants’ year of teaching experience: the ones who wanted to stay in the job, who wanted to leave the job, and who both wanted to leave and stay in the job. The findings also showed that the participants wanted to stay in the job and/or leave it for several reasons such as passion for teaching, working conditions, and learning something new, which is significant to know because understanding what may cause EL teacher attrition and retention can help sustain teacher quality in English language teaching.